Enhanced photocatalytic bacteriostatic activity towards Escherichia coli using 3D hierarchical microsphere BiOI/BiOBr under visible light irradiation. Issue 5 (22nd April 2016) - Wang, Ya; Lin, Li; Li, Fang; Chen, Liang; Chen, Donghui; Yang, Chongyang; Huang, Manhong
Abstract : With an improved separation efficiency of photogenerated holes, the BiOI/BiOBr composite exhibited enhanced photocatalytic bacteriostatic activity towards E. coli compared to the pure BiOI or BiOBr under visible light. Abstract : A BiOI/BiOBr composite was successfully fabricated by a simple hydrothermal method. The composite was characterized by X-ray diffraction (XRD), UV–vis diffuse reflectance spectroscopy (UV–vis DRS), scanning electron microscopy (SEM), and high-resolution transmission electron microscopy (HRTEM). The BiOI/BiOBr composite exhibited enhanced photocatalytic bacteriostatic activity towards E. coli compared to the pure BiOI or BiOBr under visible light irradiation. The enhanced photocatalytic performance can be attributed to the improved separation efficiency of the photogenerated holes because of its heterojunction structure. In addition, the possible bacteriostatic mechanism of the BiOI/BiOBr composite under visible light irradiation is discussed. The hierarchical microsphere BiOI/BiOBr showed enhanced photocatalytic bacteriostasis towards Escherichia coli under visible light.